Empirical safety thresholds for liquidity and indebtedness ratios on the Polish capital market - Jacek Welc (European Financial and Accounting Journal, 2016)
One of the elements of company's evaluation is ratio analysis. It includes computation of bankruptcy risk metrics. There are multiple such measures, of which two seem to be quite universal and commonly applied. These are current ratio and indebtedness ratio. In this study, the accuracy of bankruptcy predictions based on these two ratios is evaluated within a sample of data from the Polish market. Also, the safety thresholds (meant as values at which the probability of bankruptcy exceeds fifty percent) are estimated. The study is based on a sample of 84 companies, in which case a bankruptcy filing was announced in a period between the beginning of 2009 and the end of the first half of 2015. This sample of bankrupt firms is compared to the counter-sample of companies in which case no any bankruptcy filing occurred. The statistical analysis has confirmed the usefulness of both ratios. Even though the sample covers wide variety of businesses, the logit models with only one ratio used as an explanatory variable are capable of identifying bankrupt firms in about 70-73% of cases. Our research has also shown that the estimated safety thresholds lie near the typically assumed 'rules of thumb'.
Keywords: G32; G33; 650; Bankruptcy prediction; Current ratio; Financial liquidity; Fundamental analysis; Indebtedness ratio; Ratio analysis